Reusability Study of Sulfated Zirconia Functionalized SBA-15 Catalyst for Biolubricant Oil Production from Oleic Acid - Rangganita, F R; Hermida, L; Angraeni, A; Khoirunnisa, D (University of Lampung, 2019)
Sulfated zirconia functionalized SBA-15 catalsyt (SZr-SBA-15) was prepared byreacting SBA-15 with Zirkoniumoxychloride and urea at 90oC to form ZrO2-SBA-15. Then, ZrO2-SBA-15 was reacted with H2SO4 at room temperature to produceSZr-SBA-15 catalsyt.. The catalyst was characterized in terms of adsorptiondesorption nitrogen analysis, SEM-EDX and FTIR. Based on SEM-EDX andadsorption-desorption nitrogen analysis results, it was found that Zr had beenincorporated in SBA-15. By using the SZr-SBA-15 catalyst, esterification reactionof oleic acid with TMP to produce biolubricant oil of Trimethylolpropanetrioleatachieved 85% oleic acid conversion and selectivity of 63,7%. Reusability study ofSZr-SBA-15 catalyst was carried out for 3 rounds of reaction. It was found that thecatalyst could be used up to 3 rounds without significant decrease in activityKeywords: biolubricant oil, catalyst reusability, sba-15, sulfated zirconia.